Ancient Termiz in Medieval Archeology (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In this article, information about the city of Termiz and the division of ancient cities into types, the role of archaeological data in determining the location and type of the city is important. Temiz Archaeological Complex Expedition (TAKE), a scientific expedition established for the first time in Central Asia to determine the historical periods of the city of Termiz and its surroundings and to collect archaeological materials, will be told about its activities in 1936-1938.